DAILY STEP ACTIVITY METRICS AS PREDICTORS OF PREFRONTAL CORTICAL VOLUME AND EXECUTIVE FUNCTIONING IN OLDER ADULTS. (11th November 2018) - Moored, K; Leroux, A; Varma, V; Chuang, Y; Carlson, M
Abstract: Interventions that incorporate sustained, low-intensity physical activity in older adulthood have shown promise for mitigating aging-related declines in executive functioning (EF) and the prefrontal cortex (PFC)—although the benefits of low-intensity physical activity in daily life remain unclear. Recently, novel metrics have been derived from wearable activity monitors that better capture patterns in daily physical activity. One example is fragmentation, which has been shown to predict mobility and mortality in older adults. This study examined the associations between step activity metrics, PFC volume, and multiple EF measures in community-dwelling older adults. The Brain Health Study of the Baltimore Experience Corps Trial included 90 participants (age M=67.3, range:[60, 82]; 89% African-American) that completed neuropsychological tests, an MRI, and wore a step-activity monitor for three to seven days. We used this step-activity data to derive both traditional metrics (i.e., total steps) that assess average activity and novel metrics (i.e., fragmentation) of activity patterns. Prefrontal volumes were segmented using Freesurfer. All multiple linear regressions were adjusted for age, sex, education, BMI, and cardiovascular health indicators. Average total number of steps was not associated with the EF measures, p>.05. Average total number of steps was also not associated with volumes of the superior frontal, b=.07, SE=.05, p=.23, and rostral middle frontal gyri, b=.03, SE=.04, p=.38, after adjusting for intracranial volume. Average daily step activity may not predict neurocognitive correlates of EF. These results will be compared to those found using a fragmentation index, which better captures diurnal patterns of activity.